Reported health, lifestyle and clinical manifestations associated with HIV status in people from rural and urban communities in the Free State Province, South Africa - Michélle Pienaar; Francois C. van Rooyen; Corinna M. Walsh (AOSIS, 2017)
Background: HIV infection impacts heavily on the infected individual's overall health status. Aim: To determine significant health, lifestyle (smoking and alcohol use) and independent clinical manifestations associated with HIV status in rural and urban communities. Methods: Adults aged between 25 and 64 years completed a questionnaire in a structured interview with each participant. Blood specimens were analysed in an accredited laboratory using standard techniques and controls. Anthropometric measurements were determined using standardised methods. Results: Of the 567 rural participants, 97 (17.1%) were HIV-infected, and 172 (40.6%) of the 424 urban participants. More than half of HIV-infected rural participants used alcohol and more than 40% smoked. Median body mass index (BMI) of HIV-infected participants was lower than that of uninfected participants. Significantly more HIV-infected participants reported experiencing cough (rural), skin rash (urban), diarrhoea (rural and urban), vomiting (rural), loss of appetite (urban) and involuntary weight loss (rural). Significantly more HIV-uninfected participants reported diabetes mellitus (urban) and high blood pressure (rural and urban). In rural areas, HIV infection was positively associated with losing weight involuntarily (odds ratio 1.86), ever being diagnosed with tuberculosis (TB) (odds ratio 2.50) and being on TB treatment (odds ratio 3.29). In the urban sample, HIV infection was positively associated with having diarrhoea (odds ratio 2.04) and ever being diagnosed with TB (odds ratio 2.49). Conclusion: Involuntary weight loss and diarrhoea were most likely to predict the presence of HIV. In addition, present or past diagnosis of TB increased the odds of being HIV-infected. Information related to diarrhoea, weight loss and TB is easy to obtain from patients and should prompt healthcare workers to screen for HIV.